Desde una propuesta arqueológica feminista y materialista - Escoriza Mateu, Trinidad (Complutum, 2007)
A critical reflection on some contributions carried out from different feminism perspectives relating to the archaeology is proposed. Likewise we revise diverse concepts utilized such as: Patriarchy, Identity, and Social Inequality. Finally, we contribute arguments for a historical sociology since the archaeology, in relation to the objective conditions of the social life.